Kekerasan Verbal Istri pada Suami Perspektif Hukum Pidana: Studi Kasus di Dusun Srijaya Kelurahan Negara Aji Kecamatan Anak Tuha - Ayu Lestari, Putri; Setiawan, Agus; Shulton A, Habib (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Domestic violence is a crime that occurs within the scope of the household. Acts of domestic violence are not only in the form of physical and sexual assault and neglect of the household. But there are also acts of verbal/psychological violence. Anyone can be a perpetrator or victim of verbal violence, verbal violence is violence that hurts the feelings of other people, because the perpetrators of this violence are often not aware of what they are doing. Victims of domestic violence are members of the household, including the wife's behavior towards her husband. As happened to a young couple in Srijaya Hamlet, Negara Aji Tua Village, Anak Tuha District, Central Lampung Regency, namely "Wife Verbal Violence Against Husband from a Criminal Law Perspective". The purpose of this research is to examine verbal violence in the household, in terms of criminal law and to find out whether this verbal violence can be criminalized. In this study the method used was field research, the researcher conducted observations, interviews and documentation related to the wife's acts of verbal violence against her husband. Then perform data processing to be combined with various reference sources that have been prepared. According to the criminal law perspective, the results of this study are verbal violence against husbands or vice versa, which is a form of domestic violence. In the PKDRT Law, all forms of violence that occur within the household sphere are included in crimes against humanity and forms of human rights violations, so the perpetrators can be criminalized.